Design and implementation of PID controller for DC motor using PIC - Mohd Hafiz, Omar (2009)
The purpose of this study is to control the speed of direct current (DC) motor with PID controller using Proportional Integral Derivative (PID). The PID Controller will be design and must be tune, so the comparison between simulation result and experimental result can be made. The scopes includes the simulation and modeling of direct current (DC) motor, implementation of Proportional Integral Derivative (PID) Controller into actual DC motor and comparison of MATLAB simulation result with the experimental result. This research was about introducing the new ability of in estimating speed and controlling the permanent magnet direct current (PMDC) motor. In this project, PID Controller will be used to control the speed of DC motor. The PID Controller will be programmed to control the speed of DC motor at certain speed level. The sensor will be used to detect the speed of motor. Then, the result from sensor is fed back to PIC to find the comparison between the desired output and measured output to get the estimating speed.